Nomotehnika kot ovira zlorabam v pravodajnih postopkih - Kečanović, Bećir (Pravni letopis, 2013)
In the law-making process, ethical principles and moral norms pose as material sources of law. When converting ethical principles into general legal norms, nomotechnics plays an important role. The science of creating legal regulations nomotechnics, must avoid the occurrences of abuse of power and corruption. This makes the whole legal system dependent on the morality of citizens and their relation to the fundamental principles and common values. Attitudes towards ethical principles in the conduct and decisions of the legislature have a major impact on public confidence in the legislatures work, and thus the legitimacy of its decisions. In the early 21 century, the general degree of confidence in the representative bodies as the principal regulators and there by also trust in the parliamentary democracy is very low. Trust in national legislatures or parliaments in the European Union has been decreasing in the recent years, while in Slovenia the level of confidence is even lower than the average in the European Union.
Keywords: ethics; etika; legitimnost; pravni viri; zakonodaja; zaupanje